Increasing Active Participation and Engagement of Students in Circle Formations - Justin St. Onge; Karla Eitel (Networks: An Online Journal for Teacher Research, 2017)
Participation and engagement are important factors in students’ academic achievement and in increasing interest and motivation in the learning process. This study evaluates participation and engagement in circle formations in both outdoor and indoor education settings. Over a four-week study period, four instructors collected data on different circle formations. The four circle formations tested are: instructor and students standing (allstanding); instructor and students sitting (all-sitting); instructor standing with students sitting; instructor sitting with students standing. Results from 86 observation forms show that students had the greatest active participation and engagement in the all-sitting circle formation. The traditional learning arrangement, with teacher standing and students sitting, had the lowest level of student participation and engagement. Eye level of instructor and students was thought to be a major factor influencing participation and engagement in the learning environment. Results obtained from this study will help inform educators in both traditional classroom and outdoor learning environments on effective teaching practices for increasing student participation and engagement.